The Formation of undergraduate english professorship students in four universities in San Salvador in the period 2005-2007 - Ábrego Hernández, Sandra Silvia; Estupinian, Rafael Edgardo (2024)
This research presents relevant information about the formation of English undergraduate students in the period 2005-2007 and the implementation of a new modality in the English professorship career. The domain of an advance level of English for entering and the TOEFL (Test of English as a Foreign Language) for graduating as future teacher in El Salvador. At the same time, some concepts, requirements, and politics are described for the implementation of the new modality in English professorship career in the four universities that serve this career: University of El Salvador, Don Bosco, Pedagogica, and José Simeón Cañas) Besides, there is a description of the process for getting the data of the topic in study and the instruments administered for collecting all the information. The results gotten in the research express students and professors opinion about the implementation of the new modality and the advantages and disadvantages that it is implied in the process of student’s formation. The results have been analyzed in order to find out how this new implementation has affected the formation of future English teachers and the factors involved in the process. Finally, the present paper gives recommendations about the changes need to be done in some aspects in order to improve the quality of education and the fulfillment of the requisites that the Ministry of Education is demanding from English undergraduate students.